The Transition to the Single Market in the German Insurance Industry - Bernhard Mahlberg; Thomas Url (Austrian Institute of Economic Research (WIFO), 2000)
The Single Market Project of the European Commission was supposed to change the financial service industry markedly. We provide a first attempt to assess its consequences on the insurance industry in Germany, the largest insurance market within the European Union. For this purpose we apply a Data Envelopment Analysis on a panel of German insurance companies and compute efficiency scores for the years 1992 through 1996 as well as a Malmquist index for the productivity growth. The results indicate cost saving potentials and an increasing divergence between fully efficient firms and efficiency laggards. Measured scale economies imply an L-shaped average cost curve for the industry and thus low cost saving potential from further merging activities.
Keywords: L50; G22; C14; 330; European Integration; Single Market; Productivity growth; Versicherung; EU-Binnenmarkt; Deutschland